A Review of Massive Open Online Courses: MOOC's Approach to Bridge the Digital Divide - Jisoo Lee; Ahreum Hong; Junseok Hwang (International Telecommunications Society (ITS), 2018)
This paper reviews the on-going research trends of the ongoing researches conducted in various disciplines on Massive Open Online Course, or MOOC. The background overview on MOOC is organized descriptively and chronologically from the materials collected from the late 2000s to the current days. The paper then focuses on the usage of MOOC as an e-Learning open education platform in the context that it deals with the problems related to the digital divide. MOOC allows many users to participate with no cost, without spatial or temporal limitations, in online courses via the web. Thus institutes and organizations are currently showing interest in utilizing MOOC. On the contrary, there rise concerns that MOOC needs technology infrastructure and for the learner to have digital skills and language fluency. Therefore, the doubts on the linkage between MOOC and the possible solutions for digital divide arise. In this sense of MOOC having both the positive and negative influence on providing solutions for bridging the digital gap, this paper next tries to identify the current research trends of MOOC, and narrow down to what recent publications on MOOC are focused. Finally, future research proposal and the methodology is presented to pull and guide the direction of relevant studies. We propose more in-depth case studies, along with AHP method and Delphi analysis on experts' survey as future research in need.
Keywords: 330